The organisation and structure of Old English encyclopaedic notes - Kees Dekker (Filologia Germanica)
Encyclopaedic notes are difficult to define as a genre, type, or as texts falling under a certain topic. Many of them have been listed by Angus Cameron in the Plan for the Dictionary of Old English, but no definitive list has been drawn up, nor is there, amongst critics, a consensus about why they belong together. Broadly speaking, one can say that the term refers to a particular group of texts that occurs in Latin and Old English, in Anglo-Saxon manuscripts from about 800 AD onwards. In this article, I attempt, therefore, to define a category of Old English encyclopaedic notes with a distinct form, function, position and tradition within the wider field of Old English prose. For my analysis, first, an inventory of notes in Old English will be presented which contains the texts to be included in this category. Subsequently, it will be shown that although manuscript tradition and subject matter are significant, the features that distinguish encyclopaedic notes in Old English are organisation of information, linguistic structure and functionality.